Sailing to windward in Roman times: the Spritsail legacy - Davey, Christopher J. (Buried History: The Journal of the Australian Institute of Archaeology, 2016)
The iconography of Roman period merchant ships reveals them to have a different sail-plan to those of earlier times because they often have a small square sail rigged near the bow called a spritsail. The significance of the spritsail ceased to be appreciated in the early nineteenth century soon after it became obsolete. This paper discusses the role of the spritsail especially as it assisted Roman period ships to sail to windward.